The regimes of European integration constructing governance of the single market - Donnelly, Shawn (Oxford : Oxford University Press, 2010)
'The Regimes of European Integration' shows why international regimes get built or not and whether national governments delegate to the international level. It contains case studies in economic and social regulation in Germany, the UK, and within the European Union.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; European Union countries -- Economic integration; European Union countries -- Economic policy; European Union countries -- Economic conditions -- Case studies; Germany -- Economic conditions -- Case studies; Great Britain -- Economic conditions -- Case studies